2011
DOI: 10.1186/2190-4715-23-7
|View full text |Cite
|
Sign up to set email alerts
|

Systemic risks of genetically modified crops: the need for new approaches to risk assessment

Abstract: Purpose: Since more than 25 years, public dialogues, expert consultations and scientific publications have concluded that a comprehensive assessment of the implications of genetic engineering in agriculture and food production needs to include health, environmental, social and economical aspects, but only very few legal frameworks allow to assess the two latter aspects. This article aims to explain the divergence between societal debate and biosafety legislation and presents approaches to bring both together. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 63 publications
(63 reference statements)
0
12
0
Order By: Relevance
“…Wide utilization of antibiotic marker genes in GM crops led to the considerable gene flow in GM food (Hilbeck et al, 1998a,b;Losey et al, 1999;Meyer, 2011 collected from 1765 households of Mexico was also reported (Gilbert, 2013). In particular, transgene expression may influence soil biological processes and microbial community composition (Vettori et al, 2003).…”
Section: Introductionmentioning
confidence: 91%
“…Wide utilization of antibiotic marker genes in GM crops led to the considerable gene flow in GM food (Hilbeck et al, 1998a,b;Losey et al, 1999;Meyer, 2011 collected from 1765 households of Mexico was also reported (Gilbert, 2013). In particular, transgene expression may influence soil biological processes and microbial community composition (Vettori et al, 2003).…”
Section: Introductionmentioning
confidence: 91%
“…The EFSA GMO Panel also found the doses chosen for the study (11% or 33% of diet) appropriate, as they did not distort the nutritional balance of the experimental animals. We argue that the concept of substantial equivalence or the concept of familiarity, originally developed in the context of the US regulatory system for GM organisms and based on opposite assumptions as the EU regulatory system [60], is not per se applicable in the EU context. One element of this US approach is the additional use of unrelated varieties as reference controls to establish the natural variation against which GM food products need to be evaluated.…”
Section: The Need For Appropriate Regulatory Sciencesmentioning
confidence: 98%
“…the minimum number of sites or the suitable statistical models that should be applied to the dataset generated for the comparative analysis) will not be discussed further since these aspects are described in detail in previous guidance issued by the EFSA GMO Panel (EFSA GMO Panel, 2010b, 2011.…”
Section: Discussionmentioning
confidence: 99%